Bats enhance their call identities to solve the cocktail party problem - Kazuma Hase (Nature Portfolio, 2018)
Kazuma Hase et al. use microphones mounted directly on bats flying in groups to understand how they avoid confusing the echolocation signals of multiple individuals. They find that bats manipulate the terminal frequencies of their signal pulses to decrease the similarity in pulses between individuals.